Reproductive biology of air-breathing freshwater mud eel, Monopterus cuchia (Hamilton) from Bangladesh - Narejo, N T; Rahmatulllah, S M; Rashid, M Mamnur (Indian Journal of Fisheries, 2011)
Reproductive biology of an air-breathing freshwater mud eel, Monopterus cuchia (Hamilton) has been described in terms of sex- dimorphism, gonadosomatic index, ova diameter and fecundity. The specimens were collected from November 2000 to October 2001. Peaks of Gonadosomatic Index (GSI) recorded during April to June for female (7.52 1.15) and male (5.50 1.25) indicated that the fish has only one breeding season during summer. The ova diameter was found to vary from 0.30 mm to 4.0 mm. The number of ova per gram body weight was 4.61 and the number of ova present per gram of ovary weight was 74.27.